Why do Family Firms Pay Cash Dividends in Emerging Markets? Corporate Control and Family Succession in Korea - Ko, Young Kyung (Journal of Reviews on Global Economics, 2019)
Following the economic crisis in 1997, the Korean government introduced the enhanced corporate governance and reform policy, which drove family-controlled firms to search strategic reaction for control succession and wealth transfer. This paper explores alternative explanations for why Korean firms choose to pay cash dividends around this corporate reform period. What lead firms to pay cash dividends remains largely unexplained by the reducing agency cost, signaling, or life-cycle theories. This study focuses on relations between the ownership structure and cash dividends payout, seeking effects deriving from (i) controlling shareholder (CS) and (ii) their family members. The logit analysis result shows that firms with large control rights, especially higher ownership of other family members of CS are more likely to pay cash dividends. After adjusting for the characteristics that affect the degree of cash dividends, ownership variables are positively related to payout ratios and dividend yields. CS family members’ ownership has a statistically stronger effect on payout ratios than CS’s. These results provide the evidence of incentive for corporate control succession within the family with least costs carried by the family members of controlling shareholders who positively influence payout decisions and dividend ratios.